(untitled) (Bangladesh Journal of Pharmacology, 2018)
This review article aims to provide an update on the sources, pharmaco-logical and biological profile of a β-carboline alkaloid, harmine which is a major bioactive component of various plants mainly Peganum harmala. Harmine’s wide range of pharmacological properties has been well-documented as anti-cancer, anti-inflammatory, anti-oxidant, neuroprotective, anti-depressant, and antimicrobial. Although reported data suggests a multifunctional pharmacological role of harmine but farther experimentation on its molecular mechanism of action, synthetic chemistry approaches, and preclinical studies are yet obligatory to fully uncover its pharmacological efficacy.